Norway-Russia:The Svalbard Archipelago - Heininen, Lassi Kalevi; Nicol, Heather N. (ABC-CLIO, 2015)
The Svalbard Archipelago is a series of islands located in the Arctic Ocean, placed undef Norwegian administrative control By the international Spitsbergern Treaty, in 1925. While Norway's sovereign control over the archipelago itself is not disputed, its claim to control of the zone of water beyond the territorial sea is at stake.